2011
DOI: 10.1007/s11159-011-9207-y
|View full text |Cite
|
Sign up to set email alerts
|

Re-bordering spaces of trauma: auto-ethnographic reflections on the immigrant and refugee experience in an inner-city high school in Toronto

Abstract: The objective of this research study is to offer a glimpse into the lives of some newly-arrived students of different racial, linguistic and religious backgrounds as they confront the process of immigration and therefore personal and social displacement within the context of a Toronto inner-city high school. These students carry with them hidden but enduring scars that influence all aspects of their educational lives. In many cases their experience is steeped in trauma. Using autoethnographic methodology, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…When future careers or educational opportunities cannot be envisioned or foreseen, students may not be able to self-sustain motivation for long. In such contexts, the role of teachers is therefore critical in creating an effective and diverse learning atmosphere with music, drawing, games, puzzle activities, collective sports activities, story-telling, and constructive plays in order to support students and motivate them in their learning (Feuerverger, 2011;Uguak, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When future careers or educational opportunities cannot be envisioned or foreseen, students may not be able to self-sustain motivation for long. In such contexts, the role of teachers is therefore critical in creating an effective and diverse learning atmosphere with music, drawing, games, puzzle activities, collective sports activities, story-telling, and constructive plays in order to support students and motivate them in their learning (Feuerverger, 2011;Uguak, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Yau (1995) found that there was a general consensus with respect to not being able to adequately meet the needs of the growing population of refugee students that resulted from a lack of information, training, awareness of who the refugee students were, availability and access to resources, engagement with parents, and a home-school connection. More recent studies by Kanu (2008) in Manitoba, MacNevin (2012) in PEI, Dachyshyn and Kirova (2011) in Western Canada, Stewart (2012), andFeuerverger (2011) in Toronto, have echoed Yau (1995) and Kaprielian-Churchill and Churchill's (1994) findings, suggesting that these challenges continue to be barriers in meeting the needs of refugee children in Canadian classrooms.…”
Section: Teacher Awareness and Supportsmentioning
confidence: 96%
“…However, two out of three participating children, Elliott and Mason, lack visible encouragement and nurturing in regard to the relationships and places that pertain to the micro-systems that ultimately form their meso-system. Bronfenbrenner (1979) dictates that the more encouraging and nurturing these relationships and places are, the better the child will be able to develop healthily, grow-and develop learning happenings (Bronfenbrenner, 1979;Dewey, 2012;Feuerverger, 2011;Lpfö 98, 2010). Within this growth and development lies the child's ability to learn-and to find meaning in his pedagogical day (Feuerverger, 2011), something that when in the preschool setting, contrary to the parents and teachers' beliefs, was identified as absent from both Elliot's and Mason's relationships with their preschool.…”
Section: Finding 2: Meaningmentioning
confidence: 99%